Estrogen receptors in breast carcinogenesis and endocrine therapy. (15th December 2015) - Huang, Bo; Warner, Margaret; Gustafsson, Jan-Åke
Abstract: Excessive exposure to estrogen has long been associated with an increased risk for developing breast cancer and anti-estrogen therapy is the gold standard of care in the treatment of estrogen receptor (ER) α-positive breast cancers. However, there are several mysteries concerning both anti-estrogen, tamoxifen, and estrogen. The most important of these are: (1) some ERα-positive breast cancers do not respond to tamoxifen; (2) some ERα-negative breast cancers do respond to tamoxifen; (3) initial or acquired resistance to tamoxifen occurs with recurrent tumors; (4) estrogen can cause marked tumor regression in long-term tamoxifen-resistant ERα-positive breast cancer. These mysteries indicate that we do not know enough about estrogen signaling to understand the effects of targeting these receptors in cancer. The discovery of ERβ, the second estrogen receptor, has added another level of complexity to estrogen signaling. This review summarizes recent publications and makes an updated portrait of ERα and ERβ in breast carcinogenesis and endocrine cancer therapy. Highlights: ERβ is expressed in more than 50% of normal mammary epithelial cells. In invasive ductal carcinoma less than 10% of tumor cells express ERβ. Lobular breast cancer (LBrCa) expresses high levels of both ERα and ERβ. About 61% of tumor infiltrating leucocytes (TILS) express ERβ: no TILS express ERα. ERβ-selective agonists could be efficient in certain breast cancer patients.